Dirty Dollars: Profits Over Planet in Indonesia’s Application of the Polluter Pays Principle - Putra, Damar Sinatria (Faculty of Law, Universitas Negeri Semarang, 2024)
This paper critically examines Indonesia's application of the Polluter Pays Principle (PPP), revealing a troubling trend where economic interests often trump environmental responsibility. Through an in-depth analysis of case studies and regulatory frameworks, it exposes instances where corporations prioritize profits at the expense of environmental protection, exploiting regulatory loopholes and evading accountability for pollution. Drawing attention to the inherent tensions between economic development and environmental sustainability, the paper highlights the inadequacies in Indonesia's enforcement of the PPP. It scrutinizes the role of government agencies, industry actors, and civil society in perpetuating this profit-driven paradigm, shedding light on the challenges faced by environmental advocates in holding polluters accountable. Furthermore, the paper interrogates the implications of prioritizing profits over the planet, including the degradation of ecosystems, loss of biodiversity, and adverse impacts on public health and livelihoods. It underscores the urgent need for systemic reforms to align Indonesia's economic agenda with environmental imperatives, promoting a more balanced approach that prioritizes the planet alongside profits. In conclusion, the paper calls for a paradigm shift in Indonesia's application of the PPP, emphasizing the importance of robust regulations, transparent enforcement mechanisms, and corporate accountability measures. It advocates for a holistic approach that integrates environmental considerations into economic decision-making processes, safeguarding Indonesia's natural heritage for future generations while ensuring sustainable development and prosperity.